Theoretical and practical aspects of measurement and evaluation of integrated characteristics of professional competency of the pedagogue - Boyko, Іrina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article highlights the actual aspects of the interpretation of the notion of computation, competence, their use and priority directions of diagnostics of the components of professional competence of the teacher. The analysis of modern works on the competencies and competence as a multidirectional and variety of their characteristics is proved, which testifies to the very large complexity of their measurement and evaluation; an attempt was made to find ways to solve this urgent problem, which is connected with the improvement of the quality of education in the general context of its humanization. The aim is to highlight the individual professional qualities of the teacher: the general orientation of the motivational sphere, the degree of manifestation of a personal sense of professional freedom and abilities. these problems are coverage from the position of J. Raven and his emphasis on motivation and values of the individual. The role of the acmeological orientation of the individual is emphasized as an important factor in achieving pedagogical success. The acmeological orientation acts as a personal potential, which is a component of the individual psychological characteristics of the individual. The concept of personal potential has been developed in his works by D.O. Leontev and is interpreted as the ability of the individual to maintain the stability of activity under the influence of external conditions. An attempt has been made to gauge their specificity more deeply with the help of the Rorschach method. The general tendency is highlighted concerning the peculiarities of the study of the general orientation of the motivational sphere, the degree of manifestation of the personal feeling of professional freedom and abilities, which, in our opinion, is that it is relatively autonomous and its meaning lies in the field of determining the state and trends of the functioning of professional freedom, in general. Further searches are seen in solving the problem of developing effective methods for the professional diagnosis of the competence of educators in education and the creation of a continuous experimental system, which learns on the basis of own samples and errors, corrects its actions and initiates the forms of activity.
Keywords: competencies; competence; orientation of the motivational sphere; professional freedom; abilities